Farming system model for livelihood - Kashyap, Poonam; Panwar, A S; Prusty, A K; Singh, M P; Kumar, Sunil; Malik, Suresh (Indian Horticulture, 2019)
With adoption of diversified exotic vegetable-based cropping system, net returns obtained by Shri Charan Singh from 0.4 ha land increased to 119% from `92,575 to `2,03,170 with only 9.5% increase in cost of cultivation. The contribution from animal module to net income also enhanced by 26% in improved farming system, while there was significant improvement of 219% from crop module solely due to diversification by exotic vegetables as compared to existing sugarcane-based system. The benefit–cost ratio enhanced from 2.11 in existing farming system to 3.23 in improved system.